Proteins and instability elements involved in phosphoenolpyruvate carboxykinase mRNA turnover - Hajarnis, Sachin Shrikant, author; Curthoys, Norman, advisor; Bamburg, James, committee member; Mykles, Donald, committee member; Laybourn, Paul, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2006)
Phosphoerco/pyruvate carboxykinase catalyzes a rate-limiting step in hepatic and renal gluconeogenesis. However, this activity is not regulated by allosteric mechanisms or by covalent modifications. Instead, it is regulated by mechanisms that affect the level of the PEPCK m RNA and subsequently determine the level of the PEPCK protein. In the liver, various factors including glucocorticoids, thyroid hormone, and glucagon regulate the transcription of the PCK-1 gene; while in the renal proximal tubule, it is regulated by hormones including parathyroid hormone, and angiotensin II. The transcriptional regulation of the PCK-1 gene is well studied; however there is very little information about the factors that regulate the turnover of the PEPCK mRNA. Preliminary studies indicated that the 3'-UTR of the PEPCK mRNA binds to proteins from rat renal cortical cytoplasmic extracts. RNA binding proteins can modulate the levels of mRNAs by either stabilizing or targeting the mRNAs for decay. In this three-part study, we have identified the trans-acting proteins which bind to the sequences within the 3'-UTR of the PEPCK mRNA. To identify the proteins that bind to the PEPCK 3'-UTR, we employed RNA-gel shift assays, immunoblocking assays, affinity pull down assays, western blot technique and MALDI-TOF/TOF analyses. The identified proteins bind to AU- and CU-rich sequences and secondary structures found within the PEPCK 3'-UTR. A tetracycline regulated promoter system was utilized in kidney proximal tubule-like cells, to determine the instability conferred to deletion constructs of the PEPCK 3'-UTR. Northern blot analyses revealed the presence of multiple destabilizing elements within the PEPCK 3'-UTR that bind to AUF1 and/or ζ-crystallin. Acidosis leads to an seven-fold increase in the PEPCK mRNA levels, mainly through an increased transcription of the PCK-1 gene that is mediated by the activation of the p38 MAPK pathway. Our studies indicate that the activation of the p38 MAPK pathway also increases the stability of the PEPCK mRNA during chronic acidosis via its 3'-UTR. Luciferase assays and Northern blot analyses indicate that cAMP also prevents the degradation of the renal PEPCK mRNA via its 3'-UTR. Thus, taken together our studies have identified the proteins and the sequences within the 3'-U TR that determine the steady state levels of the PEPCK mRNA in response to a variety of physiological stimuli.
Keywords: molecular biology; biochemistry